Strategi Kehumasan Dalam Meningkatkan Citra Sekolah (Studi Kasus SMA Negeri 1 Plupuh Sragen) - Aldo Azanny, Varendra (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Public relations in a school environment is an important thing to pay attention to. Public relations can help improve the quality of education in schools and strengthen the relationship between students, teachers and parents. This article aims to find out the importance of public relations strategies in the school environment to build a good image. The research method uses descriptive qualitative research, data collection using interviews and observations with sampling techniques using purposive sampling, namely the head of public relations as an informant and other information that can support this research. The results showed that public relations in the SMA N 1 Plupuh school environment can improve the quality of education and strengthen relationships between students, teachers, and parents.